Islamic P2P Lending as an Alternative Solution for The Unfair Conventional Platform in Indonesia - Musjtari, Dewi Nurul; Roro, Fiska Silvia Raden; Setyowati, Ro'fah (UUM Press, 2022)
Fintech implementation still lacks legal protection for the parties involved. The rules imposed by the Financial Services Authority (FSA/ Otoritas Jasa Keuangan/OJK) have aspects of riba that contradict sharia compliance principles. This study determines alternative solutions to unfair practices in conventional Fintech, especially peer-to-peer lending (P2P lending) in Indonesian banking practices. The research uses normative and empirical methods with statutory and empirical data from library research and interviews. The study shows the presence of economic immorality in conventional P2P loan practices, such as maisyir, gharar, riba, dzalim, and haram, which are contrary to Islamic principles. This necessitates the application of primary sharia principles in sharia fintech. Thus, Islamic P2P Lending is an alternative solution to Islamic banking’s financial technology practices for customers using conventional fintech services. This is due to challenges in conventional fintech, including illegal fintech, intimidation in debt financing, high-interest rates, and the use of unlawful personal data. Therefore, the principles of sharia compliance and good faith are alternative solutions to strengthen sharia fintech and protect consumers.